Hadith Authentication Method: Concept, Application and Critique of Orientalist Skepticism - Mutammimah, Bidayatul; Husni, Muh.; Sumbulah, Umi (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2023)
Harald Motzki initiated a theory of hadith analysis called Isnad Cum Matn analysis to counter hadith criticism by orientalist groups who are skeptical of hadith. They assume that all hadiths are fake, and also assume that common links are hadith forgers. This study aims to analyze the hadith authentication method initiated by Harald Motzki. Sources of research come from the work of Motzki, books and other articles that review this theory. The results of this literature study are: 1) Moztki rejects the opinion of Gholdziher, Schacht and Juynboll who state that hadith is inauthentic; 2) A common link does not mean a forger of hadith; 3) According to Motzki, to assess the authenticity of a hadith, one must study both sanad and matn (isnad cum matn analysis); 4) This method was applied by Kamaruddin Amin to the hadith of shaum by comparing historical variants and paying attention to the characteristics of the hadith editorial staff, which finally led to the conclusion that the hadith of shaum had been spread starting in the first half of the Hijri century; 5) Motzki's critique of skeptical orientalists points to the emergence of hadith and their assumption of common link and single strand, that hadith has been the basis of law since the first century of hijriah, then common link is considered as a collector of hadith, while single strand is the most trusted path.